2023
DOI: 10.3389/fmats.2023.1253090
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity performance in sodium alginate-based Casson nanofluid flow by a curved Riga surface

K. V. Nagaraja,
K. Vinutha,
J. K. Madhukesh
et al.

Abstract: This study examines the effects of a porous media and thermal radiation on Casson-based nano liquid movement over a curved extending surface. The governing equations are simplified into a system of ODEs (ordinary differential equations) using the appropriate similarity variables. The numerical outcomes are obtained using the shooting method and Runge-Kutta Fehlbergs fourth-fifth order (RKF-45). An analysis is conducted to discuss the impact of significant nondimensional constraints on the thermal and velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Thermal radiation has wide-ranging applications in polymer processing, design of furnaces, rocket propulsion systems, and gas turbines. Many researchers have explored the consequence of radiation on MHD flow [21][22][23][24][25][26]. Implementing the Buongiorno model, Shah et al [27] have investigated the significance of nonlinear radiation on the mixed convective flow of Maxwell nanofluid induced by a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal radiation has wide-ranging applications in polymer processing, design of furnaces, rocket propulsion systems, and gas turbines. Many researchers have explored the consequence of radiation on MHD flow [21][22][23][24][25][26]. Implementing the Buongiorno model, Shah et al [27] have investigated the significance of nonlinear radiation on the mixed convective flow of Maxwell nanofluid induced by a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…A curved surface was analyzed with the application of Casson-based nanoliquid, considering the effects of porosity and thermal radiation. 30 The ordinary differential equations (ODEs) used to obtain the numerical solution for the actual problem resulted from a non-dimensional formulation. It was observed that increasing the curvature of the surface increased velocity but decreased temperature.…”
Section: Introductionmentioning
confidence: 99%